Management of presacral retroperitoneal schwannoma: highlighting the various features - Dhangar, Sanjay P.; Baste, Nitin; Murumkar, Sandeep P.; Shengal, Manisha (International Surgery Journal, 2020)
Schwannomas are relatively rare tumours. They occur in approximately 1 of 40,000 hospital admissions. Usually asymptomatic unless very big in size. They may present with symptoms of visceral compression viz. constipation, urinary frequency and urgency, or the nerve compression like sciatica, lower extremity weakness, tingling and numbness. We here highlight the various clinical, radiological and pathologic features the tumour and importance of proper pre-operative imaging, planning regarding surgery and the type of consent required before the surgery in a 30 years old male with a large pelvic mass, diagnosed and supposed to be Schwannoma arising from the S2 sacral foramina. We were able to enucleate the mass intact without any visceral or neuro-vascular injury with minimal blood loss.